Ridisegnare la soggettività. Sulla lettura derridiana di Valéry - Papparo, Felice Ciro (Bollettino Filosofico, 2021)
This paper wants to address the Derrida’s deconstructive – as well as articulated and well-founded – “reading” of the thought of Paul Valéry, focusing on the Cahiers and recovering two key-concepts contained therein: the voice and the implex. By reviewing the “aversions” of Valéry toward Freud and Nietzsche, as well as their “proximities”, both highlighted by Derrida in his text, we would like to re-establish the complexity and multiformity of both “notions”, bringing them back to their syntactic-conceptual root, which is peculiar to the Valerian way of thinking. In our view, indeed, when compared to the typical tone of Valéry’s reasoning, there is something “forced” in the hermeneutic grid used by Derrida, which risks to “veil” the problematic and critical aim that underlies the Valéry’s “rethinking” of the status of “subjectuality”, when he tries to locate – in the voice as well as in the implex – the “unerasable” marks of subjectual “doing”, a doing understood as a properly human poietic-poetic attitude, aimed at a re-construction and re-configuration of one’s own field of existence – beyond the stereotypies and exhibitionisms of an individual clinging to his own venerated figure. Keywords: Implex, Psychoanalysis, Subjectuality, Valéry, Voice